Banana Peel Bio-Battery Project-Based Electronic Worksheet: Enhancing Creative Thinking and Psychomotor Skills - M. Arya Nata Raharjo; Kartini Herlina; B. Anggit Wicaksono (Universitas Muhammadiyah Sidoarjo, 2025)
This study aims to develop a project-based electronic student worksheet on banana peel bio-battery (hereinafter referred to as a project-based e-LKPD) to process banana peel waste into a simple bio-battery and to examine its validity, practicality, and effectiveness in improving students’ creative thinking and psychomotor skills. The product was developed using the 4D model (Define, Design, Develop, Disseminate) and grounded in Social Constructivism theory. It was tested on 15 Grade X high school students. Validation by material, media, and learning experts yielded an average score of 3.29 (on a 1–4 scale), indicating very good quality in terms of content and instructional design. Practicality was assessed through readability (97%), student questionnaire responses (95%), and teacher perceptions (88.09%), confirming that the project-based e-LKPD is easy to use, well-received, and allows students to complete project tasks with minimal difficulty. The effectiveness test showed an average score of 82.1 for creative thinking skills and 75.2 for psychomotor skills (both on a 0–100 scale), demonstrating significant improvement in both competencies. These results confirm that the project-based e-LKPD on banana peel bio-battery is valid, practical, and effective as an innovative learning tool to promote higher-order thinking, hands-on skills, environmental awareness, and understanding of renewable energy.